Razmerje med ekonomskimi svoboščinami in pravico do sindikalnih ukrepov pred Lizbonsko pogodbo in po njej - Ščernjavič, Iztok (Podjetje in delo, 2013)
The author analyses the EU Court of Justice approach to balancing the economic freedoms with the right to take industrial (collective) action. He argues that the relationship between this right and economic freedoms is actually hierarchical, even though the Court of Justice emphasizes that the right to take industrial action is a fundamental right and therefore equivalent to economic freedoms. Furthermore, the author discusses the question whether the binding nature of Charter of Fundamental Rights of the EU (Charter) and the EU's accession to the European Convention on Human Rights (ECHR) will have an impact on the existing relationship between the right to take industrial action and economic freedoms. The author concludes that the binding nature of the Charter and the EU's accession to the ECHR will probably even increase the existing gap between actual and declared protection of the right to take industrial action.
Keywords: European Union; Evropska unija; Lizbonska pogodba; mednarodne pogodbe; pravice; sindikati; zaposleni